b)
[tex]x=\frac{\frac{1}{2}-\frac{1}{4}}{\frac{1}{2}-\frac{2}{5}}=\frac{\frac{1}{4}}{\frac{1}{10}}=\frac{5}{2}\\y=\frac{2\frac{1}{5}-\frac{1}{4}}{2\frac{1}{2}-\frac{1}{4}}=\frac{\frac{44}{20}-\frac{5}{20}}{\frac{9}{4}}=\frac{39}{20}\cdot\frac{4}{9}=\frac{13}{15}\\z=\frac{1\frac{1}{3}+\frac{1}{2}}{1\frac{2}{3}+\frac{1}{4}}=\frac{\frac{4}{3}+\frac{1}{2}}{\frac{5}{3}+\frac{1}{4}}=\frac{\frac{11}{6}}{\frac{23}{12}}=\frac{11}{6}\cdot\frac{12}{23}=\frac{22}{23}[/tex]
Najdłuższy jest odcinek x i widać, że
x>y+z, albowiem x=2.5 natomiast y<1 i z<1, czyli y+z<2 i nie ma potrzeba nawet dokładnie tego liczyć
pozdrawiam